THE USE OF TELEMEDICINE IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Yuliana Noviyanti; Dewi Ilma Antawati (P3I UMSurabaya, 2024)
This article reviews evidence-based studies on the effectiveness of telemedicine in Tele-mental Health (TMH) or telepsychology across various community groups. The review, sourced from Google Scholar using keywords such as coparenting determinant, telemedicine, mental health, consultation, digitalization, and clinical psychologist, aims to provide a scientific basis for integrating mental health services with technology. Telemedicine, which involves long-distance communication through telephones and video conferencing, offers an alternative to reach wider communities and bridge gaps in service accessibility. The implementation of telepsychology in Indonesia considers factors such as professionalism, infrastructure, multiculturalism, and the competence of psychologists. Findings indicate that telepsychology is as effective as face-to-face therapy in terms of treatment outcomes, but it is more cost-effective and accessible, particularly in remote areas. Further research is needed to assess the effectiveness of TMH in Indonesia, especially for severe mental health disorders.